2012
DOI: 10.1111/hel.12028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori Eradication on Circulating Adiponectin in Humans

Abstract: Eradication therapy of H. pylori increased circulating adiponectin levels in Japanese individuals and could be beneficial for preventing metabolic syndrome conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…Paired liver biopsies are required to provide core evidence on histological endpoints, that is, hepatic steatosis, inflammation, and mainly fibrosis, regarded as the main histological endpoint for advanced disease . Importantly, total adiponectin and all its isoforms were increased after successful H pylori eradication treatment in humans, a finding that further supports the beginning of clinical trials, since adiponectin upregulation exhibits anti‐steatotic, anti‐inflammatory, anti‐fibrotic, and anti‐apoptotic effect in NAFLD . In this regard, thiazolidinediones (pioglitazone and rosiglitazone), which have shown beneficial effect on NAFLD histology, act at least partly through adiponectin upregulation .…”
Section: Closing Remarkssupporting
confidence: 53%
“…Paired liver biopsies are required to provide core evidence on histological endpoints, that is, hepatic steatosis, inflammation, and mainly fibrosis, regarded as the main histological endpoint for advanced disease . Importantly, total adiponectin and all its isoforms were increased after successful H pylori eradication treatment in humans, a finding that further supports the beginning of clinical trials, since adiponectin upregulation exhibits anti‐steatotic, anti‐inflammatory, anti‐fibrotic, and anti‐apoptotic effect in NAFLD . In this regard, thiazolidinediones (pioglitazone and rosiglitazone), which have shown beneficial effect on NAFLD histology, act at least partly through adiponectin upregulation .…”
Section: Closing Remarkssupporting
confidence: 53%
“…Adiponectin, an adipocyte‐derived hormone, reduces lipid storage in the liver and protects against inflammation and fibrosis . Many studies suggested that patients with H. pylori infection have lower adiponectin levels, and H. pylori eradication can lead to an increase in adiponectin levels . Low serum adiponectin levels would contribute to the development of NAFLD .…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 338 ones had HP and underwent treatment. The serum level of adiponectin had no statistically significant difference in HP positive and negative patients but HP eradication increased the adiponectin level [27]. …”
Section: Discussionmentioning
confidence: 99%